Brain activity during traditional textbook and audiovisual‐3D learning. Issue 10 (30th September 2019) - Pujol, Jesus; Blanco‐Hinojo, Laura; Martínez‐Vilavella, Gerard; Canu‐Martín, Lucila; Pujol, Anna; Pérez‐Sola, Víctor; Deus, Joan
Abstract: Introduction: Audiovisual educational tools have increasingly been used during the past years to complement and compete with traditional textbooks. However, little is known as to how the brain processes didactic information presented in different formats. We directly assessed brain activity during learning using both traditional textbook and audiovisual‐3D material. Methods: A homogeneous sample of 30 young adults with active study habits was assessed. Educational material on the subject of Cardiology was adapted to be presented during the acquisition of functional MRI. Results: When tested after image acquisition, participants obtained similar examination scores for both formats. Evoked brain activity was robust during both traditional textbook and audiovisual‐3D lessons, but a greater number of brain systems were implicated in the processing of audiovisual‐3D information, consistent with its multisource sensory nature. However, learning was not associated with group mean brain activations, but was instead predicted by distinct functional MRI signal changes in the frontal lobes and showed distinct cognitive correlates. In the audiovisual‐3D version, examination scores were positively correlated with late‐evoked prefrontal cortex activity and working memory, and negatively correlated with language‐related frontal areas and verbal memory. As for the traditional textbook version, the fewer results obtained suggested the opposite pattern, with examination scores negatively correlating with prefrontal cortex activity evoked during the lesson. Conclusions: Overall, the results indicate that a similar level of knowledge may be achieved via different cognitive strategies. In our experiment, audiovisual learning appeared to benefit from prefrontal executive resources (as opposed to memorizing verbal information) more than traditional textbook learning. Abstract : We report the neural correlates of traditional textbook and audiovisual learning. A similar level of knowledge may be achieved with both educational formats. Audiovisual learning benefits from executive resources more than from verbal memory.